Multi-sensory Responsiveness and Personality Traits Predict Daily Pain Sensitivity - Bar-Shalita, Tami; Cermak, Sharon A. (Frontiers in Integrative Neuroscience, 2020)
Background A continuous effort has been devoted to identifying factors that contribute to individual differences in pain perception. Amongst the personality traits, Neuroticism is assumed to be the most significant moderator of experimental and clinical pain. Multi-sensory responsiveness to daily sensations has been shown to be associated with pain perception. Yet, neither the relationship between personality traits and multi-sensory responsiveness, nor the impact of both these factors to pain perception have been examined. Thus, this study aims to explore the contribution of both multi-sensory responsiveness and personality traits to pain perception in a daily context. Methods A community-based sample of 204 adults completed the Sensory Responsiveness Questionnaire - Intensity Scale (SRQ-IS); the Big Five Inventory (BFI); and the Pain Sensitivity Questionnaire (PSQ). Results The partial eta-square demonstrated that the SRQ-IS Aversive sub-scale score had the strongest relationship with the PSQ-Total score, accounting for 9% of the variation. The regression coefficient relating PSQ-Total score with SRQ-IS Aversive, and BFI sub-scales of Extraversion, Neuroticism and Openness-to-Experience scores was found to be r = 0.39 (p<0.0001), accounting for 16% of the variance, and yielding a large effect size. Discussion To the best of our knowledge this is the first study to report on the interplay between aversive responsiveness to daily sensations and personality traits of Neuroticism, Openness-to-Experience and Extraversion as contributing factors to daily pain sensitivity, amongst which aversive responsiveness was found as the major contributing factor. This study may broaden the understanding of the pain experience variability, both in practice and in experimental research.